Interest groups and health care reform across the United States - Gray, Virginia, 1945-; Lowery, David, 1952-; Benz, Jennifer K. (American governance and public policy., 2013)
Universal health care was on the national political agenda for nearly a hundred years until a comprehensive (but not universal) health care reform bill supported by President Obama passed in 2010. The most common explanation for the failure of past reform efforts is that special interests were continually able to block reform by lobbying lawmakers. Yet, beginning in the 1970s, accelerating with the failure of the Clinton health care plan, and continuing through the passage of the Affordable Care Act in 2010, health policy reform was alive and well at the state level. This book assesses the impact of interest groups to determine if collectively they are capable of shaping policy in their own interests or whether they influence policy only at the margins. What can this tell us about the true power of interest groups in this policy arena? The fact that state governments took action in health policy in spite of opposing interests, where the national government could not, offers a compelling puzzle that will be of special interest to scholars and students of public policy, health policy, and state politics.